A cost-effective ROF system employing FBG and DML to generate optical mm-wave - Nguyen, Viet Hoang; Huang, Cheng (Photonics Letters of Poland, 2013)
We have investigated and experimentally demonstrated a ROF system employing FBG and low-cost DML to generate optical mm-wave. We employ FBG because the bandwidth of the optical modulator is largely reduced and the architecture of the ROF system is simpler. Because no expensive broadband external modulator is used, the overall system is considered as a cost-effective solution. This novel scheme employs low-cost DML to generate mm-wave signal which is a practical scheme to be applied for future broadband access networks. Full Text: PDF References L. Xu and T. Wang, "Key technologies for high-speed digital coherent optical communications", Proc. ICO, pp. 1?2, May, (2011). CrossRef S. Mikel and L. Alayn, "Orthogonally polarized optical single sideband modulation for microwave photonics processing using stimulated Brillouin scattering", Opt. Express, vol. 18, no. 22, pp. 22906?22914, (2010). CrossRef Z. Cao, J. Yu, M. Xia, Q. Tang, Y. Gao, W. Wang, and L. Chen, "Reduction of Intersubcarrier Interference and Frequency-Selective Fading in OFDM-ROF Systems", J. Lightw. Technol., vol. 28, no. 16, 2423?2429, Aug. 15, (2010). CrossRef J. Yu, et al., "Cost-Effective Optical Millimeter Technologies and Field Demonstrations for Very High Throughput Wireless-Over-Fiber Access Systems", J. Lightw. Technol., vol. 28, no. 16, pp. 2376?2397, Aug. 15, (2010). CrossRef C. Tsekrekos, T. Kuri, and K. Kitayama, "Distribution of Millimeter-Wave and Baseband Services Over an Integrated Reconfigurable Access Network Platform", J. Lightw. Technol., vol. 28, no. 19, pp. 2783?2790, Oct. 1, (2010). CrossRef Z. Dong, J. Lu, Y. Pi, X. Lei, L. Chen, and J. Yu, "Optical millimeter-wave signal generation and wavelength reuse for upstream connection in radio-over-fiber systems", Journal of Optical Networking, 7, 736-741, (2008). CrossRef W. Jiang, C. T. Lin, A. Ng'oma, P. T. Shih, J. Chen, M. Sauer, F. Annunziata and S. Chi, "Simple 14-Gb/s Short-Range Radio-Over-Fiber System Employing a Single-Electrode MZM for 60-GHz Wireless Applications", J Lightw Technol., vol.28, no. 16, 2238-2246, (2010). CrossRef J. Ma, "5 Gbit/s Full-Duplex Radio-Over-Fiber Link With Optical Millimeter-Wave Generation by Quadrupling the Frequency of the Electrical RF Carrier", J. Opt. Commun. Netw., vol.3, no. 2, 127-133, (2011). CrossRef Z. Cao, J. Yu, H. Zhou, W. Wang, M. Xia, J. Wang, Q. Tang and L. Chen, "WDM-RoF-PON Architecture for Flexible Wireless and Wire-Line Layout", J. Opt. Commun. Netw., vol. 2, no. 2, 117-121, (2010). CrossRef J. Yu, J. Gu, X. Liu, Z. Jia, G. Chang, "Seamless integration of an 8×2.5 Gb/s WDM-PON and radio-over-fiber using all-optical up-conversion based on Raman-assisted FWM", IEEE Photon. Technol. Lett. 17, 1986-1988, (2005). CrossRef J. Seo, Y. Seo, W. Choi, "1.244-gb/s data distribution in 60-GHz remote optical frequency up-conversion systems", IEEE Photon. Technol. Lett. 18, 1389-1391, (2006). CrossRef J. Yu, Z. Jia, G. Chang, "All-optical mixer based on cross-absorption modulation in electroabsorption modulator", IEEE Photon. Technol. Lett. 18, 2421-2423, (2005). CrossRef H. Song, J. Lee, "Error-free simultaneous all-optical upconversion of WDM radio-over-fiber signals ", IEEE Photon. Technol. Lett. 17, 1731-1733, (2005). CrossRef J. Yu, Z. Jia, L. Yi, Y. Su, G. Chang, "Optical millimeter-wave generation or up-conversion using external modulators", IEEE Photon. Technol. Lett. 18, 265-267, (2006). CrossRef Jianjun Yu, Z. Jia, L. Xu, L.Chen, T. Wang, and G. K, Chang, "DWDM optical millimeter-wave generation for radio-over-fiber using an optical phase modulator and an optical interleaver", IEEE Photon. Technol. Lett. 18, 1418- 1420, (2006). CrossRef M. Attygalle, C. Lim, G. Pendock, A. Nirmalathas and G. Edvell, "Transmission improvement in fiber wireless links using fiber Bragg gratings", IEEE Photon. Technol. Lett. 17, 190- 192, (2005). CrossRef L. Chen, J. He, Y. Li, H. Wen, Y. Shao, C. Huang, L. Hu, Y. Pi, Z. Dong, Y. Li, X. Lei and S. Wen, "Simple ROF configuration to simultaneously realize optical millimeter-wave signal generation and source-free base station operation", ECOC, vol.2, 45-46, (2007) . DirectLink